1991
DOI: 10.1177/070674379103600913
|View full text |Cite
|
Sign up to set email alerts
|

Autism: Its Primary Psychological and Neurological Deficit

Abstract: Autism is a perplexing condition because of its unique presenting signs and high degree of variability. Evidence is presented that the basic underlying information processing disorder is a dysfunction of the appreciation of the emotional significance of incoming stimuli and attaching motivational value to the stimuli. It is proposed that this dysfunction occurs when the amygdaloid nucleus and/or its connections are disrupted, resulting in the variability of the presentation of this syndrome among individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Our results thus lend support to the notion that atypical amygdala function may play a central role in the neuropathology characterising the disorder (e.g. Bachevallier, 1994;Bachevallier, 2000;Baron-Cohen et al, 1999;Baron-Cohen et al, 2000;Fotheringham, 1991;Howard, et al, 2000;Sweeten, et al, 2002). However, rather than a basic amygdala abnormality, our findings suggest that atypical amygdala function may arise from poor connectivity between this structure and functionally associated cortical areas.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Our results thus lend support to the notion that atypical amygdala function may play a central role in the neuropathology characterising the disorder (e.g. Bachevallier, 1994;Bachevallier, 2000;Baron-Cohen et al, 1999;Baron-Cohen et al, 2000;Fotheringham, 1991;Howard, et al, 2000;Sweeten, et al, 2002). However, rather than a basic amygdala abnormality, our findings suggest that atypical amygdala function may arise from poor connectivity between this structure and functionally associated cortical areas.…”
Section: Discussionsupporting
confidence: 43%
“…Although several lines of research have implicated the amygdala in the pathology underlying this disorder (e.g. Bachevallier, 1994;Bachevallier, 2000;Baron-Cohen et al, 1999;Baron-Cohen, Ring, Bullmore, Wheelwright, Ashwin, & Williams, 2000;Fotheringham, 1991;Howard, et al, 2000;Sweeten, Posey, Shekhar & McDougle, 2002), the evidence is somewhat inconsistent and the extent and nature of the proposed amygdala pathology remain unclear (see Sweeten et al, 2002;Amaral, Bauman & Mills Schumann, 2003;Palmen, van Engeland, Hof & Schmitz, 2004 for recent reviews). Fear conditioning paradigms are valuable in this respect because different forms of conditioned fear behaviour have been shown to rely on different amygdala nuclei or pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Fein and colleagues (1987) have argued that dysfunction of the amygdala in autism results in disruption of the ability to assign meaning to social stimuli. Similarly, Fotheringham (1991) suggested that dysfunction of the amygdala in autism brings about a failure to appreciate the normal motivational and emotional significance of stimuli. These formulations are compatible with the theoretical positions of Hobson (1992) and Loveland (1991, both of whom have argued that for people with autism the world is not meaningful in the same ways as for other people.…”
Section: Is the Orbitofrontal-amygdala Circuit Dysfunctional In Autism?mentioning
confidence: 97%
“…A range of theories have been proposed to account for the cognitive impairment in autism, including inability to comprehend the perspectives of others ("theory of mind") (Baron- Cohen et al, 1985), inability to utilize context in understanding the environment ("central coherence") (Frith and Happé, 1994;Happé, 1994), inability to process emotional information (Fotheringham, 1991;Hobson, 1991;Hobson, 1993;Beversdorf et al, 1998), impaired executive function (Rumsey, 1985;Rumsey and Hamburger, 1988;Rumsey and Hamburger, 1990), and global/local processing biases toward the local (Mottron and Burack, 2001), among others. As a manifestation of decreased utilization of context, research has supported the hypothesis that individuals with ASD have a restriction of flexibility of access to the semantic network, including decreased semantic clustering in verbal memory (Minshew and Goldstein, 2001), lack of increased recall of words when syntactic and semantic context is added (O'Connor and Hermelin, 1967;Hermelin and O'Connor, 1970;Hermelin and Frith, 1991), as well as superior performance on the "false memory" task (where the semantic and associative relationships between a heard word list and a not presented lure induce a false memory for the lure in typical individuals) (Beversdorf et al, 2000), despite a more typical performance by the same participants on most other cognitive tests for autism (Beversdorf et al, 1998).…”
Section: Noradrenergic System Cognition and Autismmentioning
confidence: 98%